The wages of affluence : - Gordon, Andrew (Harvard University Press, 1998)
This is a major achievement, and confirms Andrew Gordon's place as a truly outstanding scholar of Japanese labour history...The overwhelming richness of the written and interview material marshalled to discuss these questions makes compelling reading. Industrial relations history is deftly interwoven with the broader social and political context of the time. Indeed, the control for the workplace spilled over into the home, the streets, the courts and even the arena of international relations. Those wishing to understand the post-war remaking of Japan's political economy and society will find much of value in this book